Tenofovir clearance is reduced in HIV-positive patients with subclinical tubular impairment. (27th March 2016) - Calcagno, Andrea; Cusato, Jessica; Marinaro, Letizia; Simiele, Marco; Lucchiari, Manuela; Alcantarini, Chiara; Tettoni, Maria C.; Trentini, Laura; Mengozzi, Giulio; D'Avolio, Antonio; Di Perri, Giovanni; Bonora, Stefano
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To assess if tenofovir (TFV) clearance is associated with urinary retinal-binding protein (RBP) in HIV-positive patients with normal estimated filtration rate. Design: A cross-sectional diagnostic study. Methods: HIV-positive patients with estimated creatinine clearance above 60 ml/min, on tenofovir disoproxil fumarate (TDF)-containing combination since at least 6 months, taking TDF at night, and without significant comorbidities (diabetes, untreated hypertension, known renal malformations, recurrent nephrolithiasis) and nephrotoxic drugs were included. TFV plasma and urinary concentrations were measured 12 h after drug intake (C12 ). RBP was measured through enzyme immunoassay kit on spot urines and corrected per urinary creatinine (uRBP/uCr); normality ranges were below 130 μg/g (in patients aged <50 years) and below 172 μg/g (in patients aged ≥50 years). Results: Two hundred and eighty-nine patients were included (median age of 45.8 years, 71.6% male and 85.4% whites); patients were concomitantly treated with nonnucleoside reverse transcriptase inhibitors (155, 53.6%), protease inhibitors (118, 40.8%), or integrase inhibitors (16, 5.5%)-containing regimens. Estimated creatinine clearance was 89.4 ml/min (78.6–105.9). Urinary RBP (uRBP) and uRBP/uCr were 204.6 ng/ml (92–380) and 169.7 μg/g (85.8–318.3), respectively; abnormally high uRBP/uCr was observed in 157 patients (54.3%). A multivariate binary logistic regression confirmed that both ethnicity ( P  = 0.004, β 2.93, 95% confidence interval 1.41–6.10) and TFV urinary C12 less than 21 mg/ml ( P  = 0.006, β 2.04, 95% confidence interval 1.12–3.41) were significantly associated with abnormal uRBP/uCr. Conclusion: HIV-positive TDF-treated patients showed a high prevalence of proximal tubular impairment: ethnicity (whites) and low urinary TFV concentrations were significantly associated with elevated uRBP. SDC video: http://links.lww.com/QAD/A852 .